MANAJEMEN PENGEMBANGAN MUTU PENDIDIK MENGHADAPI TANTANGAN ERA REVOLUSI DIGITAL 5.0 OLEH KEPALA SEKOLAH DI SMK BINA CENDEKIA ASTANA JAPURA KABUPATEN CIREBON JAWA BARAT - Huriyah; Yayat Suryatna; Ika Yuniatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to 1. Describe the managerial role of the principal of SMK Bina Cendekia in welcoming the era of society 5.0 2. Describe the methods used by the principal 3. Describe the inhibiting and supporting factors of teaching. This research is a qualitative descriptive study. Data collection was carried out through interviews, observation and documentation studies. The data analysis process is carried out by reducing the data that has been collected and checking the data is carried out through data triangulation. The results of the research show that the managerial role of the principal at SMK Bina Cendekia begins at the planning where at this stage the principal determines the ratio between the number of students and teaching staff in a class. The next is the selection of teaching staff whose criteria accordance with the era of society 5.0. The next managerial stage for the principal is developing the career of teaching staff by including IT-based seminars. The method applied by the school principal is giving authority to teaching staff to implement the required learning systems and techniques, requiring teaching staff to involve the school committee and parents and guardians of students in every school activities, carrying out curriculum development, evaluating the performance of teaching staff, and collaborating with external parties to provide digital-based training. There are some inhibiting factors in improving the quality of teaching staff, there are the teaching staff's understanding of technological sophistication, and differences in the ages of teaching staff. On the other hands the supporting factor is the high enthusiasm of the teaching staff in attending technology-based training or workshops organized by the school principal.